Synergistic improvement of thermal conductivity in polymer composites filled with pitch based carbon fiber and graphene nanoplatelets - Noh, Ye Ji; Kim, Seong Yun (ELSEVIER SCI LTD, 2015)
We found that the thermal conductivity of composite materials was synergistically enhanced by the simultaneous incorporation of well-dispersed pitch-based carbon fibers (PCFs) and graphene nanoplatelets (GNPs) into the matrix. Accordingly, this study investigated the causes of such enhancement and attempted to optimize the thermal conductivity. The solvent-free composites fabrication method based on powder mixing and in-situ polymerization proposed recently was employed to achieve a uniform dispersion of fillers of different sizes and shapes. The isotropic and in-plane thermal conductivity of the composite containing both uniformly dispersed 5 wt% of PCF and 15wt% of GNP achieved improvements of 82% and 183% when compared to those containing 20 wt% of GNP, and improvements of 65% and 74% when compared to those containing 20 wt% of PCF, respectively. The synergistic improvement of the thermal conductivity was maximized at the optimized composition due to the most efficient formation of thermally-conductive pathways and internal structures favorable for phonon transport. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: THERMOPLASTIC COMPOSITES; MECHANICAL-PROPERTIES; THEORETICAL APPROACH; BORON-NITRIDE; DISPERSION; FABRICATION; MATRIX; HEAT